Weed Control in Pepper - William M. Stall; James P. Gilreath (EDIS, 2006)
Revised! HS-199, a 5-page fact sheet by William M. Stall and James P. Gilreath, describes a weed control program that integrates chemical, mechanical, and cultural methods and provides a table of listing herbicides available to growers for chemical weed control of pepper. This publication updates the 2003 tables to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.